Intellectual Capital and Earnings Quality: Do They Connect? - Rachma Bhakti Utami; Nila Firdausi Nuzula; Cacik Rut Damayanti (Pusat P2M Politeknik Negeri Batam, 2023)
The main objective of this research is to look at the relationship between intellectual capital and earnings quality in Indonesian banks. Intellectual capital is measured by using EVAIC+, where the indicators consist of Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Relational Capital Efficiency (RCE), and Capital Employed Efficiency (CEE). Earnings quality is measured using discretionary accruals and earnings persistence. Furthermore, this study also looks at whether there is a difference in the effect of intellectual capital on earnings quality based on the type of bank, in this case, State-Owned and Private Banks. The objects of this study were eight banks, consisting of four state-owned banks and four private banks, and this study examines a total of 112 banking samples in Indonesia. The researcher used the Partial Least Square Multigroup technique to analyze this study, with research data for 2006 - 2019. The results showed that intellectual capital was essential for influencing banking earnings in Indonesia. This study also shows that the intellectual capital analyzed separately between state-owned and private banks has a significant and positive effect on earnings quality, meaning that the type of bank does not moderate the effect of the independent variables on the dependent variable in this study. This study recommends more budget allocation to intellectual capital to create quality profits in banks in Indonesia.